ANALISIS KELAYAKAN USAHATANI CABE JAWA (Peeper retrofractum) Di RESORT WONOASRI TAMAN NASIONAL MERU BETIRI (TNMB) KABUPATEN JEMBER - Deby Rimba Samudra Fernandez Dacosta; Luh Putu Suciati; Djoko Soejono (Jember University Press, 2019)
ABSTRACT One of the supporters of the national parks of Meru Betiri National Park (TNMB) in land rehabilitation is for the purpose of enhancing the ability and independence community in benefiting forest resource and land optimally. Chilli plant is a plant endemic to Java, which is in the Meru Betiri National Park National Park (TNMB) in addition Java is chili plants intercrop in Meru Betiri National Park as it can grow under the shade of a tree of principal. In addition the existence of the programme planning of aquaculture farming Java Chilli can also increase the income of farmers in land rehabilitation of Meru Betiri National Park National Park (TNMB). This research aims to know the: (1) financial feasibility analysis of effort of land rehabilitation Resort Java Chilli Wonoasri Meru Betiri National Park National Park (TNMB) District Jember; (2) the sensitivity of farming Java Chili against the decline in production and a decrease in the price of production. The research results showed that: (1) analysis ofthe feasibility of farming chili Java at Resort Wonoasri Garden Meru Betiri National Park (TNMB) with the investment criteria of Jember District shows the result with the value as follows: Net Present Value (NPV) worth Rp 94,783,796; PR worth 13.63; Net benefit Cost (Net/B/C) worth 13.63; Gross Benefit Cost Ratio (Gross B/C) worth 3.71 and Internal Rate of Return (IRR) is worth 43.7%. Based on the results of financial eligibility criteria then Java chili farming deserves to be run and developed. (2) J ava chili farming is not sensitive to a decrease in production of 40% so that the Java chili farming is still eligible to run and developed and insensitive Java chili farming is taking action against a price reduction of 18%.Keywords: Java Chili, Feasibility Analysis, Sensitivity Analysis ABSTRAK Salah satu kegiatan pendukung Taman Nasional Meru Betiri (TNMB) di lahan rehabilitasi adalah dengan tujuan untuk meningkatkan kemampuan dan kemandirian masyarakat dalam mendapatkan manfaat sumberdaya hutan dan lahan secara optimal. Tanaman cabe jawa merupakan tanaman endemik yang berada di kawasan Taman Nasional Meru Betiri (TNMB) selain itu tanaman cabe jawa merupakan tanaman sela di Taman Nasional Meru Betiri karena dapat tumbuh dibawah naungan pohon pokok. Selain itu dengan adanya program tersebut perencanaan budidaya usahatani cabe jawa juga dapat meningkatkan pendapatan petani di lahan rehabilitasi Taman Nasional Meru Betiri (TNMB). Penelitian ini bertujuan untuk mengetahui: (1) analisis kelayakan finansial usaha cabe jawa lahan rehabilitasi Resort Wonoasri Taman Nasional Meru Betiri (TNMB) Kabupaten Jember; (2) sensitivitas usahatani cabe jawa terhadap penurunan produksi dan penurunan harga produksi. Hasil penelitianmenunjukan bahwa: (1) analisis kelayakan usahatani cabe jawa di Resort Wonoasri Taman Nasional Meru Betiri (TNMB) Kabupaten Jember dengan kriteria investasi menunjukkan hasil dengan nilai sebagai berikut: Net Present Value (NPV) bernilai Rp 94.783.796; PR bernilai 13,63; Net benefit Cost (Net B/C) bernilai 13,63; Gross Benefit Cost Ratio (Gross B/C) bernilai 3, 71 dan Internal Rate of Return (IRR) bernilai 43,7%. Berdasarkan hasil kriteria kelayakan finansial maka usahatani cabe jawa layak untuk dijalankan dan dikembangkan. (2) Usahatani cabe jawa tidak peka terhadap penurunan produksi sebesar 40% sehingga usahatani cabe jawa masih layak untuk dijalankan dan dikembangkan dan usahatani cabe jawa tidak peka tehadap penurunan harga sebesar 18%. Kata Kunci: Cabe Jawa, Analisis Kelayakan, Analisis Sensitiitas.